Kant and his German contemporaries / Volume 2 Aesthetics, history, politics, and religion / edited by Daniel O. Dahlstrom - Dyck, Corey W. (Kant and his German contemporaries, 2018)
Kant's philosophical achievements have long overshadowed those of his German contemporaries, often to the point of concealing his contemporaries' influence upon him. This volume of new essays draws on recent research into the rich complexity of eighteenth-century German thought, examining key figures in the development of aesthetics and art history, the philosophy of history and education, political philosophy, and the philosophy of religion. The essays range over numerous thinkers including Baumgarten, Mendelssohn, Meyer, Winckelmann, Herder, Schiller, Hamann and Fichte, showing how they variously influenced, challenged, and revised Kant's philosophy, at times moving it in novel directions unacceptable to the magister himself. The volume will be valuable for all who are interested in this distinctive period of German philosophy